Comprehensive analysis of proteomic and biochemical responses of Daphnia magna to short-term exposure to polystyrene microplastic particles - Young Sang Kwon; Chang-Beom Park; Seung-Min Lee; Jin-Woo Park; Yeong-Jin Kim; Jong-Hwan Kim; Jong-Su Seo (Ecotoxicology and Environmental Safety)
Microplastic (MP) represent a pervasive and escalating threat to aquatic ecosystems, impacting organisms from cellular to population levels. To investigate the immediate molecular impacts of MP exposure, we exposed Daphnia magna, a keystone species in freshwater ecosystems, to polystyrene microplastic particles (5 μm, 5 μg/L) for 48 h. Through proteomic and biochemical analyses, we identified extensive disruptions in key physiological pathways. Notably, proteins involved in energy metabolism, including glycolysis and the tricarboxylic acid (TCA) cycle, were downregulated, suggesting a metabolic shift away from growth-related processes. Elevated levels of oxidative stress markers such as superoxide dismutase, catalase, and glutathione reductase reflected a pronounced response to reactive oxygen species. The upregulation of endocytosis-related proteins, including caveolin-1 (CAV1) and phosphatidylinositol-4-phosphate 5-kinase (PIP5K), highlights their role in actively internalizing and compartmentalizing MP, potentially as a protective mechanism against oxidative damage. These findings reveal that short-term MP exposure triggers a complex, multi-pathway stress response in D. magna, underscoring potential vulnerabilities that could impact broader ecological dynamics. This study emphasizes the urgency of understanding MP toxicity to guide environmental policies and conservation efforts aimed at mitigating the effects of plastic pollution.